KEPATUHAN PETUGAS DALAM MENERAPKANPROTOKOL KESEHATAN CEGAH COVID-19 DI RS XYZ - Murniati, Nia; Salsanabilla, Wafiqa (Jurnal Vokasi Indonesia, 2021)
Health behavior change is a learning process from, by, and to help oneself from a health problem where the cause of behavior change depends on the quality of the stimulus given. Compliance of health workers with health protocols to prevent Covid-19 is an important concern in efforts to break the chain of spread of Covid- 19. Compliance with the implementation of the COVID-19 health protocol is an application for the security and safety of hospital staff in providing services to patients. The massive spread of the COVID-19 virus has the potential to spread from patients to all hospital staff. The lack of discipline in implementing the COVID-19 health protocol in hospitals such as wearing masks not according to standards, not maintaining distance, not applying proper cough etiquette, not avoiding crowds, and not using PPE according to standards resulted in hospital staff being very vulnerable to the risk of transmission. This study aims to compare the compliance of patient care workers with back office officers in implementing the COVID-19 health protocol, using quantitative methods with univariate analysis and qualitative methods through interviews with PPI officers at XYZ Hospital. The results showed that the compliance of patient care workers (79.2%) was higher than that of back office staff (77.5%).